TRANSFORMASI DIGITAL DALAM ERA GLOBALISASI - Dinda Annisa Putri (PUTRA JAWA PUBLISHER, 2024)
E-Business has become an inevitable phenomenon in the modern business world. In this article, we discuss the concepts, benefits and challenges associated with e-business. We also outline the role of digital transformation in accelerating the adoption of e-business in the era of globalization. The data used in this article comes from literature research and reliable sources related to e-business. Digital transformation refers to the fundamental changes that occur in society and the economy due to the growing use of digital technology. In the era of globalization, digital transformation is becoming increasingly important due to its widespread and potential impact in changing the way we live, work and interact. In the context of globalization, digital technologies play a key role in connecting individuals, organizations and countries globally. The internet and digital communications enable fast and easy access to information, overcome geographical boundaries, and enable more effective collaboration among stakeholders from different parts of the world. Digital transformation has also changed the business landscape globally. Companies that can adapt quickly to changes in digital technologies and utilize them to improve operational efficiency, develop new business models, and provide better customer experiences, have a competitive advantage in an increasingly competitive global marketplace.